Evaluating organ preservation outcome as treatment endpoint for T1aN0 glottic cancer. (25th October 2016) - Low, Tsu‐Hui (Hubert); Yeh, David; Zhang, Tina; Araslanova, Rakhna; Hammond, J. Alex; Palma, David; Read, Nancy; Venkatesan, Varagur; MacNeil, S. Danielle; Yoo, John; Nichols, Anthony; Fung, Kevin
Abstract : Objectives/Hypothesis: Common endpoints in reporting the outcomes for early glottic cancer do not highlight the importance of organ preservation. We evaluated the treatment outcomes among patients with T1aN0 laryngeal cancer with laryngectomy‐free disease‐specific survival (LFS‐DSS), which is defined as time to total laryngectomy or time to death from cancer cause, against all other endpoints. Study Design: Outcome research on an institutional database. Methods: A retrospective review covered all consecutive patients from 2003 to 2013. Patients with T1a laryngeal squamous cell carcinoma (SCC) were offered the options of either radiation treatment (RT) or transoral laser microsurgery (TLM). Tumor control, survival outcomes, standard definition laryngectomy‐free survival (LFS), and LFS‐DSS were calculated. Results: There were 105 patients, of whom 53 were treated with TLM and 52 were treated with RT. There were 11 recurrences within the TLM group, of which four were successfully salvaged with repeated TLM and two were salvaged with RT. Among the four recurrences within the RT group, all four patients had salvage total laryngectomies. The 5‐year overall survival for patients treated with TLM versus RT was 86% versus 85% ( P = .887), disease‐free survival was 69% versus 78% ( P = .151), LFS was 65% versus 77% ( P = .198), LFS‐DSS was 100% versus 88% ( P = .030), and ultimate locoregional control was 100% in both groups. Conclusions: Patients with T1aN0 glottic SCC treated with RT or TLM have similar survival outcomes. Patients with T1a tumor treated with TLM have better organ preservation compared to RT, when measured with LFS‐DSS. Level of Evidence: 4. Laryngoscope, 127:1322–1327, 2017